SANKSI ALTERNATIF BAGI PELAKU KEKERASAN SEKSUAL TERHADAP ANAK YANG TIDAK LAYAK DIKENAKAN TINDAKAN KEBIRI KIMIA - Amodra Mahardika Putra Widianto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
The issuance of Government Regulation Number 70 of 2020 concerning Procedures for Carrying Out Chemical Castration, Installation of Electronic Detection Devices, Rehabilitation, and Announcement of the Identity of Perpetrators of Sexual Violence Against Children, becomes a legal certainty for the implementation of Article 81 of the Child Protection Act. However, after the regulation was enacted, there was a problem, namely that the convict could not be subject to chemical castration because there were factors from the convict himself. This study uses normative juridical research and is supported by interview data and uses statutory and conceptual approaches. This research aims to contribute knowledge in the science of criminal law and is useful for law enforcement practitioners regarding alternative sanctions that can be imposed on perpetrators of sexual violence against children. The results of the study show that the convict may not be subject to chemical castration due to psychological disorders or medical abnormalities in the convict. Therefore, it is necessary to have alternative sanctions in the form of action sanctions that refer to Article 103 of Law Number 1 of 2023 concerning the Criminal Code (KUHP). If deemed necessary, derivative regulations can be issued to accommodate the imposition of alternative sanctions such as Supreme Court regulations and Attorney General regulations.